Penguatan Literasi Dasar di Sekolah Dasar Desa Toapaya : Sebagai Fondasi Pendidikan Berbasis Kolaborasi dan Integrasi - Annisa Valentina; PinaLestari; Zaidan Muharramain3; Aulia Agustin4; Femiliana Agnes; Isnovera Asdayanti; Aldi Junaidi; Febriyanti Halawa; Rachel Immanuela Simanjuntak; Feny Natal Situmorang (Pusat Riset dan Inovasi Nasional, 2025)
Literacy is a fundamental skill essential for academic, social, and cultural development, yet interest in and culture surrounding literacy remain low in rural areas such as Desa Toapaya, Indonesia. This community service program aimed to strengthen basic literacy at SDN 005 Toapaya through a collaborative and integrative approach involving the school, university students, the Bintan Library Office, families, and local communities. The method employed was participatory and collaborative, implementing the SIBER CERDAS program (Synergy of Interactive Learning, Literacy, and Numeracy), which included shared reading, interactive discussions, quizzes, writing and storytelling competitions, and interactive numeracy activities. The results showed increased student motivation and participation in literacy and numeracy activities, as well as improved confidence in oral expression. Additionally, there was a noticeable improvement in students’ engagement with reading materials. Challenges faced included limited reading materials, inconsistent literacy habits at home, and lack of awareness about the importance of regular literacy practice. To ensure sustainability, ongoing support from schools, families, and local government, along with strengthened cooperation with libraries and communities, is necessary. Encouraging active participation and fostering a habit of regular reading is crucial for the long-term success of such initiatives. This program successfully created an inclusive and sustainable literacy ecosystem and serves as an adaptable model for similar rural communities, offering valuable lessons in community-driven educational development.